Evaluasi Efektivitas Tempat Tidur Tahun 2019-2024 Di Rumah Sakit Pelabuhan Jakarta - Salsabella, Pradita; Iqbal, Muhammad Fuad; Fannya, Puteri; Dewi, Deasy Rosmala (Politeknik Negeri Jember, 2025)
The effectiveness of bed utilization is a key indicator of inpatient service quality. Fluctuations in the number of beds at Pelabuhan Hospital Jakarta from 2019 to 2024 have affected the Bed Occupancy Rate (BOR), which remains below the ideal standard. This study aims to evaluate bed utilization effectiveness during that period using a descriptive quantitative method based on inpatient census data. Results showed that the number of beds in each ward fluctuated, with an average BOR ranging from 37% to 74%. The Turnover Interval (TOI) and Average Length of Stay (AvLOS) were generally within the ideal range, while the Bed Turnover (BTO) tended to be high. Changes in bed numbers had varying effects on BOR: an average increase of 3.8 beds raised BOR by 22.8%, while an increase of 5 beds reduced it by 8.4%. Conversely, reducing 2.6 beds increased BOR by 7.2%, while reducing 2 beds decreased it by 19.3%. Bed procurement was carried out through an official memorandum from the nursing unit to the director based on service trends and needs. Therefore, bed planning should use predictive methods and historical data analysis over a minimum of three to five years.